Handbook of research on representing health and medicine in modern media - Sari, Gulsah, 1984- (Advances in linguistics and communication studies (ALCS) book series., 2021)
"This book is intended to provide a snapshot of the current state of representation of health and medicine in media, offering a resource for those in the field of health communication"--